2023
DOI: 10.3389/fphar.2023.1167418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel lncRNA prognostic signature and analysis of functional lncRNA AC115619.1 in hepatocellular carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is the deadliest malignancy. Long non-coding RNAs (lncRNAs) are involved in the development of multiple human malignancies. This study aimed to establish a reliable signature and identify novel biomarkers for HCC patients.Methods: Differentially expressed lncRNAs (DElncRNAs) were identified from Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases. Univariate, LASSO, and multivariate Cox regression analyses were applied to screen the prognostic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“… 12 Recent studies discovered that lncRNAs have aberrant expressions in tumor tissues and body fluids. 13 As peripheral blood is the most widely used specimen for tumor diagnosis, numerous studies have attempted to identify blood biomarkers for cancer diagnosis owing to easy accessibility, nonintrusiveness, and low cost. 14 Studies have reported several serum or plasma exosomal lncRNAs with the potential to be new minimally invasive markers for the early diagnosis of different cancers, including HCC.…”
Section: Introductionmentioning
confidence: 99%
“… 12 Recent studies discovered that lncRNAs have aberrant expressions in tumor tissues and body fluids. 13 As peripheral blood is the most widely used specimen for tumor diagnosis, numerous studies have attempted to identify blood biomarkers for cancer diagnosis owing to easy accessibility, nonintrusiveness, and low cost. 14 Studies have reported several serum or plasma exosomal lncRNAs with the potential to be new minimally invasive markers for the early diagnosis of different cancers, including HCC.…”
Section: Introductionmentioning
confidence: 99%